Analysis of Factors Affecting Indicators of Community Welfare in South Sulawesi Using Path Analysis Method - Sauddin, Adnan; Adiatma, Adiatma; Nurliani, Nurliani (Bulletin of Economic Studies (BEST), 2022)
The welfare of the community can be measured by several indicators such as education, health, economy, employment, etc. It’s indicators that have been established as indicators of community welfare by the Central Statistics Agency (BPS) that can support national development. This research aims to analyze the factors that influence the indicators of community welfare using the path analysis method. The results of the analysis show that health indicators significantly influence economic indicators, in this case GRDP and employment indicators which are measured through the workforce level with the scope of research is South Sulawesi. Keywords: Community Welfare, Education, Health, Labor Force, GRDP, Path Analysis